Toxicity of chloroform extracts of Derris indica Bennet. against Callosobruchus maculatus (F.) adults - Mondal, Omar Ali; Islam, Nurul (University Journal of Zoology, Rajshahi University, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> No Abstract Key words: Toxicity, Derris indica, Chloroform extract, Callosobruchus maculatus doi:10.3329/ujzru.v27i0.1963 Univ. j. zool. Rajshahi Univ. Vol. 27, 2008 pp. 95-96